Medical Marijuana From Medicine, Legal And Islamic Law Perspective: A Review - Siti Fatimah Nordin; Fatimah Zanirah Nordin; Mohammad Naqib Hamdan; Mohd Rahman Omar (USIM PRESS, 2024)
VOL. 34 NO. 3 (2022)